LUDRUK SEBAGAI MEDIA MENGABARKAN MISI KERAJAAN ALLAH DI LINGKUP GREJA KRISTEN JAWI WETAN - Dwi Ratna Kusumaningdyah; Firman Panjaitan (Manna Rafflesia, 2023)
This study aims to explain ludruk culture as a means to preach the mission of the Kingdom of God in the scope of Jawi Wetan Christian Church (GKJW). Generally, the play/story ludruk revolves around social criticism of people's lives, with the aim of improvement in the lives of these people. Using the qualitative – descriptive method, this study shows the intersection point in the story ludruk with the mission of the Kingdom of God, so that ludruk can be used as a cultural foundation to bring the mission of the Kingdom of God on Earth East Java. The results showed that ludruk and the mission of the Kingdom of God are an appropriate synergy for GKJW to preach the mission of the Kingdom of God.